Representasi Masyarakat Sumatera dalam Novel "Harimau! Harimau!" Karya Mochtar Lubis - M. Syirojudin A'malina Wijaya (Jurnal Bahasa Lingua Scientia, 2018)
Harimau! Harimau! is a novel by Mochtar Lubis published in 1975. Mochtar Lubis himself is a writer born in Padang, West Sumatra. As a Sumatran man, his works mostly depict Sumatra, especially in the harimau! harimau!. This study aims to explore the representation of Sumatran society in the novel Harimau! Harimau! by Mochtar Lubis. This research uses the method of sociology literature approach, it is because this research seeks to examine the link between literature with the reality of society in various dimensions. In the research, there is a depiction of the expertise of treating, music, food processing, geography, and the beliefs of the Sumatran society depicted by Mochtar Lubis in his novel Harimau! Harimau!